2019
DOI: 10.3390/ijms20020251
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization and Identification of Trihelix Transcription Factor and Expression Profiling in Response to Abiotic Stresses in Rice (Oryza sativa L.)

Abstract: Trihelix transcription factors play a role in plant growth, development and various stress responses. Here, we identified 41 trihelix family genes in the rice genome. These OsMSLs (Myb/SANT-LIKE) were located on twelve chromosomes. Synteny analysis indicated only six duplicated gene pairs in the rice trihelix family. Phylogenetic analysis of these OsMSLs and the trihelix genes from other species divided them into five clusters. OsMSLs from different groups significantly diverged in terms of gene structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 56 publications
10
45
0
Order By: Relevance
“…GT-2 and SH4 clades contained eight and six MtGT members, respectively. These results were similar to the genes distribution of different subgroups in Arabidopsis and rice [12,23].…”
Section: Phylogenetic Analysis and Classification Of Mtgt Genessupporting
confidence: 85%
See 2 more Smart Citations
“…GT-2 and SH4 clades contained eight and six MtGT members, respectively. These results were similar to the genes distribution of different subgroups in Arabidopsis and rice [12,23].…”
Section: Phylogenetic Analysis and Classification Of Mtgt Genessupporting
confidence: 85%
“…Recently, a few more trihelix TFs have been characterized which played important roles in multiple processes during plant growth and development, such as trichome development [ 14 ], shattering of the mature seed during crop domestication [ 17 ], morphogenesis control of floral organs [ 13 ], and response to abiotic and biotic stresses [ 15 , 18 ]. In this study, we identified 38 MtGT genes in M. truncatula , which is similar to the number of trihelix genes in Arabidopsis (30) [ 12 ], rice (41) [ 23 ], and tomato (36) [ 24 ]. Additionally, it is close to the average number of trihelix genes on each subgenome of wheat (31) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only six duplication events were found, and tandem duplications were found among three BdGT gene pairs, such as BdGT16 and BdGT24 , BdGT19 and BdGT26 , and BdGT20 and BdGT28 . The results suggest BdGT genes were less conserved, implying most genes might not originate from the same ancestor, which was consist with the report in rice [12]. Gene synteny analysis showed that almost all B. distachyon GT genes (except BdGT12 ) showed a syntenic relationship with those in rice, maize, and Arabidopsis , implying this family genes had a high degree of retention following whole-genome duplication (Figure 6).…”
Section: Discussionsupporting
confidence: 77%
“…The GT genes have been systematically studied in model plants such as Arabidopsis , tomato, soybean, chrysanthemum and rice. For instance, there are 30 members in Arabidopsis , 36 in tomato, 63 in soybean, 20 in chrysanthemum, and 41 in rice [5,10,11,12,13]. Generally, these family members contain a conserved DNA-binding domain, which has three tandem helices (helix-loop-helix-loop-helix) that combine specifically with the GT elements, a light-responsive DNA element [14].…”
Section: Introductionmentioning
confidence: 99%